Nano metal additive enhanced magnetorheological fluid based on rheological and thermophysical properties - Mohd Salleh, Abdul Rahim (2020)
Controllable rheological properties through external magnetic field makes magnetorheological materials useful in many applications such as brakes and clutches. However, the performance of magnetorheological fluid is affected by heat generation due to operating condition and particle friction. The heat must be dissipated by producing magnetorheological fluid with enhanced thermal conductivity. This study aims to develop stabilized nano metal added magnetorheological fluid for enhanced thermal conductivity and to evaluate the effects of nano metal added magnetorheological fluid on magnetorheological response. The materials for this study were the nano metal added magnetorheological fluid with fumed silica additive. The materials were prepared with specific concentration of suggested components by using two-step method. 10 samples were developed under three different categories namely MRF, MRF-Cu, and MRF-Al. Experiments were designed based on combined D-optimal model for mixture design with the target to optimize the configuration of magnetorheological fluid for high sedimentation ratio and high thermal conductivity. The study started with investigation of sedimentation ratio through visual observation method. Sedimentation of synthesized samples was observed by inspecting the sediment for 28 days. Then, the study followed with investigation of thermal conductivity in the absence and the presence of magnetic field. The investigation was conducted by thermal properties analyzer and by a module that was based on guarded hot-plate method. The module was developed due to the limitations of thermal properties analyzer in measuring thermal conductivity under magnetic field. Next, the study was finalized with determination of magnetorheological response in the presence of magnetic field. The rheological response was conducted by rheometer and the magnetization response was conducted by vibrating sample magnetometer. The results from every investigation were compared with the commercial MRF-132DG. From the sedimentation ratio investigation, the sample with 5% aluminum recorded the highest enhancement at 14% due to the low density of aluminum particles and the addition of fumed silica. From the thermal conductivity investigation, the highest thermal conductivity without magnetic field was recorded at 0.902 W/m·K from the sample with 5% copper due to the high thermal conductivity value of copper material and its particle size. The enhancement from the sample was 153%. By using the developed module, the sample showed an increase from 0.925 W/m·K without magnetic field to 1.102 W/m·K with magnetic field. The result was from the effect of the chain-like structures formed by the particles when experiencing magnetization. The sample has the highest enhancement at 137% due to the maximum concentration of copper. Finally, from the magnetorheological response determination, the sample with 5% copper demonstrated the highest shear stress (90.3 kPa) in the presence of magnetic field with 276% enhancement due to the higher number of particle chains. The sample recorded the highest magnetization (30.98 emu) and magnetic saturation with 71% enhancement. The addition of copper nanoparticles has avoided the formation of aggregates from magnetic particles by forming clouds around each magnetic particle and resulted to stronger bonds between the particles. The findings in this work provided encouraging results of enhanced magnetorheological fluid properties. With optimized configuration of magnetorheological fluid components, the addition of nano metal additive has enhanced the sedimentation ratio, thermal conductivity, and magnetorheological responses. Hence, nano metal added magnetorheological fluid is suitable to be used for improved performance in elevated temperature applications. It is recommended that redispersibility of the nano metal added magnetorheological fluid is investigated in the future.